1-(3,5-Dinitrobenzoyl)-3,3-dipropylthiourea - Saeed, Sohail (International Union of Crystallography, 2011)
The title thiourea derivative, C(14)H(18)N(4)O(5)S, features two substantial twists between its component fragments: the dihedral angle between the SN(2)C (thiourea) and ONC(2) (amide) residues is 48.89 (7)° and that between the benzene ring and the amide residue is 30.27 (7)°. In the crystal, molecules are linked by bifurcated N—H⋯(O,S) hydrogen bonds, generating [001] supramolecular chains.